Traumatic accidents - Danza, Rómulo; Arias, José (Cirugía del Uruguay, 1973)
1) Twenty cases of surgery due to traumatism of a large artery leading to the limbs, are studied. 2) Sixteen of these cases presented associated lesions: osteo-artícular, in soft and nervous parts. 3) Lesion producing mechanisms are analyzed ( a ,;ast majority are due to work accidents) as well as topography of lesions. 4) Identification of surgical cases and operatory opportunity are discussed. 5) Conduct to be followed with respect to arterial lesions is studied, it should tend to re-establish flow procedures employed were venous graft (14 cases); arterial suture (3 cases) or adventicectomy (3 cases) in cases of contusion with arterial spasm. 6) Conduct before osteo-articular lesions in soft or associated nervous parts is analyzed. 7) Results are listed, with 16 total restorations, 3 sequella due to associated lesions, 1 amputation due to distal attrition and no cases of death or thrombosis ín repaired arterial sector.